2015
DOI: 10.1128/mcb.01249-14
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence-Specific Interaction between the Saccharomyces cerevisiae rRNA Gene Repeats and a Locus Encoding an RNA Polymerase I Subunit Affects Ribosomal DNA Stability

Abstract: The spatial organization of eukaryotic genomes is linked to their functions. However, how individual features of the global spatial structure contribute to nuclear function remains largely unknown. We previously identified a high-frequency interchromosomal interaction within the Saccharomyces cerevisiae genome that occurs between the intergenic spacer of the ribosomal DNA (rDNA) repeats and the intergenic sequence between the locus encoding the second largest RNA polymerase I subunit and a lysine tRNA gene [i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…This pattern of rDNA-gene contacts might partially explain the observation that genes whose expression was correlated with rDNA CN included several candidates encoding the protein components of the ribosome. Indeed, sequence specific inter-chromosomal interactions between the yeast rDNA array and an intergenic segment adjacent to the largest RNA pol I subunit has recently been demonstrated [ 30 ]. All in all, our study identified functionally coherent genes and GO categories that are depleted and enriched in direct rDNA contacts.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of rDNA-gene contacts might partially explain the observation that genes whose expression was correlated with rDNA CN included several candidates encoding the protein components of the ribosome. Indeed, sequence specific inter-chromosomal interactions between the yeast rDNA array and an intergenic segment adjacent to the largest RNA pol I subunit has recently been demonstrated [ 30 ]. All in all, our study identified functionally coherent genes and GO categories that are depleted and enriched in direct rDNA contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are intergenic regions between the genes in rDNA cluster (see Figure 3A), IGS1 contains an origin of DNA replication (rARS) while IGS2 includes both the replication fork barrier (RFB) and a bidirectional RNA polymerase II-dependent promoter (Kobayashi and Sasaki, 2017). In addition, it has been revealed that IGS1 is also responsible for maintenance of nucleolar stability along with stabilization of rDNA repeat number (Cahyani et al, 2015). The disruption of even a few rDNA repeats among the hundreds of copies gained through evolutionary processes can therefore affect cell fitness and hinder strain development.…”
Section: Rdna Clusters and Its Coupling With Crispr/cas9mentioning
confidence: 99%
“…In yeast, only about half of the ~150 rDNA repeats are actively transcribed to meet the translational needs of the cell [ 7 ]. Although only about half of these repeats are actively transcribed, it is known that in budding yeast, reduced copy number makes cells more sensitive to DNA damage [ 3 ].The extra, untranscribed copies are thought to contribute to stability and integrity of the locus by acting as a ‘foothold’ for repair enzymes and for contacts with other regions of the genome [ 3 , 8 10 ]. Human population genome sequencing data analysis has revealed correlations between rDNA copy number and the expression of several genes encoding chromatin-modifying proteins [ 11 ], further supporting the idea that the effects of rDNA copy number go well beyond rRNA production for ribosome biogenesis.…”
Section: Introductionmentioning
confidence: 99%